Asymmetric electrostatic environment around spacecraft in weakly streaming plasmas. Issue 8 (20th August 2015) - Miyake, Y.; Nishimura, Y.; Kasaba, Y.
Abstract The double‐probe electric field measurements in drifting plasmas are subject to spurious effects caused by asymmetric electrostatic structure near scientific spacecraft. Some in situ observations just outside the plasmasphere detected spurious electric fields due to such environmental asymmetry even in subsonic ion flows across the magnetic field line. We have performed three‐dimensional particle‐in‐cell simulations, which allow us to include long and extremely thin wire booms as well as a spacecraft chassis, and investigated an electrostatic environment that accounts for the observations. The present simulations reveal that even subsonic ion flows can produce an appreciable potential difference between the upstream and downstream sides of the spacecraft, and the potential difference would be detected as a spurious field of a few mV/m. The necessary condition for the spurious field is a relatively high (a few tens of V) spacecraft potential, and also the spacecraft potential hump needs to be expanded by thin wire booms biased at the spacecraft potential. The analysis also reveals that the presence of a heavy ion flow and a field‐aligned ion upflow can further enhance the spurious field up to 5 mV/m.